Non-Performing Financing (NPF) at Islamic Pawnshop of Indonesia: A Systematic Literature Review - Izzatul Muna; Yusuf DINC (Journal of Management Economic and Financial, 2026)
Islamic pawnshops in Indonesia play an important role in providing pawn-based financing alternatives that are in accordance with sharia principles. Despite rapid development, the sector faces serious challenges in managing Non-Performing Financing (NPF). High NPF indicates gaps in the implementation of sharia principles and can threaten the financial stability of institutions. This research aims to identify the factors influencing NPF at Pegadaian Syariah and provide recommendations for improving financing management. Some factors that influence NPF include risk management, inappropriate selection of contract types, and low customer understanding of Islamic contracts. Additionally, macroeconomic factors such as the impact of the Covid-19 pandemic have further worsened this situation. To address this issue, there needs to be an increase in Islamic financial literacy, a strengthening of the customer selection system, and better application of information technology to monitor problematic financing. The findings of this research are expected to help Pegadaian Syariah reduce NPF and maintain its financial health.